CNS Organoid Surpasses Cell-Laden Microgel Assembly to Promote Spinal Cord Injury Repair - Zitian Wang; Haoran Zhao; Xiaowei Tang; Tianyu Meng; Davit Khutsishvili; Bing Xu; Shaohua Ma (Research, 2022)
The choice of therapeutic agents remains an unsolved issue in the repair of spinal cord injury. In this work, various agents and configurations were investigated and compared for their performance in promoting nerve regeneration, including bead assembly and bulk gel of collagen and Matrigel, under acellular and cell-laden conditions, and cerebral organoid (CO) as the in vitro preorganized agent. First, in Matrigel-based agents and the CO transplantations, the recipient animal gained more axon regeneration and the higher Basso, Beattie, and Bresnahan (BBB) scoring than the grafted collagen gels. Second, new nerves more uniformly infiltrated into the transplants in bead form assembly than the molded chunks. Third, the materials loaded the neural progenitor cells (NPCs) or the CO implantation groups received more regenerated nerve fibers than their acellular counterparts, suggesting the necessity to transplant exogenous cells for large trauma (e.g., a 5 mm long spinal cord transect). In addition, the activated microglial cells might benefit from neural regeneration after receiving CO transplantation in the recipient animals. The organoid augmentation may suggest that in vitro maturation of a microtissue complex is necessary before transplantation and proposes organoids as the premium therapeutic agents for nerve regeneration.